Keśavacandra Sena : suprasiddha samāja-sudhāraka aura Brahma-dharma ke dhundhara pracāraka Mahātmā Keśavacandra Sena kī jīvanī - Caturvedī, Banārasīdāsa, 1892-1985 (SAMP early 20th-century Indian books project, 1919)
On the life and work of Keshub Chunder Sen, 1838-1884, social reformer and Hindu religious leader.